A phenomenological hermeneutic investigation into the psychoanalytic psychotherapist's experience of using the psychoanalytic couch - Milton, Christopher (Rhodes University, Faculty of Humanities, Department of Psychology, 2004)
The aim of this study was to describe and critically explore the psychoanalytic, psychotherapist's lived experience of the technique of using the couch. Through examination of the literature a question was formulated that would disclose the analyst's experience of the technique of using the couch. Four experienced psychoanalytic practitioners who could be operationally defined as 'analysts' were interviewed. Using a phenomenological method the protocols were comprehensively analyzed to produce descriptions of the general structure of the experience. These were then texturally enhanced using interleaved direct citations from the interviews. The structural and textural 'findings ' so produced were then hermeneutically dialogued with contemporary psychoanalytic notions of critical discourse and intersubjectivity. The phenomenological ' findings ' of the study disclosed the meaning of the couch as context-based, paradoxical and ambiguous. The couch was found to be a symbol of the analyst as analyst and the process as authentic analysis. Furthermore, at its best, the couch was found to mediate a mode of being that is containing and intimate and in which psychological life may be evoked, tracked and interpreted. The most significant contributor to this mode of being was found to be privacy, which, in particular, helps the analyst maintain an analytic attitude. The couch was also found to be significantly implicated in the generation of an intersubjective analytic third and to support reverie. These 'findings' were hermeneutically dialogued with literature on the couch as well as contemporary psychoanalytic theoretical notions. The dialogue fell into three foci. The first focus entailed deconstructing the meaning of the couch as context-based and ambiguous and not essential. The second pursued critiques of the role that the couch plays in domination, of its function as a symbol/evocative object and of the way in which it shapes being-together, bodily attunement, privacy, the intersubjective analytic third and reverie. Finally the 'findings' were critically examined in terms of both Lacan's notion 'analytic discourse ' and its role in revealing/concealing the analysand as subject. The study concludes with an examination of its own limitations and suggestions for further research.
Keywords: Freud, Sigmund, 1856-1939 -- Criticism and interpretation; Psychoanalysis; Psychotherapy; Psychotherapy -- Methods